Influencing Factors on the Stability of Direct Methanol Fuel Cells. Issue 6 (4th December 2019) - Jing, F.; Sun, R.; Wang, S.; Li, Y.; Yang, C.; Ma, W.; Sun, H.; Sun, G.
Abstract: This work investigated the influencing factors on the stability of direct methanol fuel cells via testing a single‐cell, which was conducted at 60 °C under 100 mA cm −2 for 3, 009 h. To completely uncover and interpret the performance degradation mechanism, electrochemical method (such as polarization curve, electrochemical impedance spectra, anode polarization voltammetry, methanol crossover and cyclic voltammetry tests), electron microscopy technique (SEM, TEM and EDX) and XRD spectroscopy were coherently performed in this work. The degradation rate in the whole test process is relatively steady, in which the cell voltage decreases 29% and the maximum power density decreases 35%. However, there is obviously an irreversible degradation when the cell runs at about 1, 600 h. According to our analysis, the irreversible degradation of the cell is mainly caused by the increase of resistance and decrease of catalytic activity. Further, the increase of the resistance might be due to the increase of the interface resistance between cathode and Nafion ® membrane according to SEM results. In addition, the decrease of catalytic activity is mostly caused by Ru loss from anode side to cathode side and the agglomeration of catalyst particles in both electrodes.